Perancangan Model Peningkatan Kinerja Pada PT. Bank ANZ Indonesia - Tutik Winarsih (ITB AAS INDONESIA Surakarta, 2021)
This research abstract aims to design the integrity model of PBSC and OBSC in determining the priority of corrective action at ANZ Bank Indonesia Sales Comercial Banking Division. This study uses qualitative approach with case study method. The type of research used in this study is a type of 'description research'. Design research design of PBSC and OBSC integration model to determine the priority of corrective action at ANZ Bank Indonesia Sales Commercial Banking Division. The results showed that in the external perspective of improvement of ANZ Indonesia Bank organizationally with the same perspective becomes a priority is to develop programs for goal-oriented marketing. In the perspective of knowledge and learning organizationally with the same perspective the priority is to conduct planning interviews, training and assessments with employees based on individual performance plans and capability profiles. In a financial perspective the priority is to close an unprofitable business unit. Keywords: TPS, Organizational Balanced Scorecard, PBSC, Perspective Internal, External, Knowledge and Learning, Finance